Cross-cultural validation of the performance failure appraisal inventory-short form: a Malaysian adaptation / Santhosh Ayathupady Mohanan - Mohanan, Santhosh Ayathupady (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2012)
The purpose of the present study was to examine the cross-cultural validity of the short version of the Performance Failure Appraisal Inventory (PFAI; Conroy, 2001; Conroy, Willow, & Metzler, 2002) by analyzing reliability and validity of a Malay language (official language of Malaysia) translation. Three studies were performed to translate the inventory and examine its factorial invariance and criterion validity. A total of 509 Malaysian athletes participating in various sports participated. In study 1, the hypothesized single factor model was examined performing a confirmatory factor analysis using Structural Equation Modelling (SEM). The criterion validity was examined by comparing fear of failure scores with the scores of achievement goals. Cronbach’s alpha values indicating internal consistency reliability was high (α = .93). Altogether, it was concluded that the Malay adaptation of the Performance Failure Appraisal Inventory-Short form (PFAI-SM) yielded reliability and validity that evidenced support for the cross-cultural usefulness of the scale.